2018
DOI: 10.1186/s41936-018-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism underlying the neurotoxicity induced by sodium fluoride and its reversal by epigallocatechin gallate in the rat hippocampus: involvement of NrF2/Keap-1 signaling pathway

Abstract: Background: Fluoride (Fl) exposure engenders neurodegeneration and induces oxidative stress in the brain. Therefore, the mechanism of Fl-induced neurotoxic effects needs to be determined. The aim of this study was to investigate the neuroprotective effects of EGCG (40 mg/kg) on Fl (25 mg/kg/bw)-induced oxidative stress mediated neurotoxicity with special emphasis on the hippocampus (4 weeks).Results: Fl-intoxicated rat shows an increased Fl concentration along with the decreased neurotransmitter (AChE, NP, DA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Epigallocatechin gallate (EGCG) found in tea, particularly green tea, is a flavonoid characterized by very string antioxidative properties. A study revealed a very significant increase in the enzymatic and non-enzymatic antioxidative properties as well as a decrease of oxidative stress indicators in the brains of rats poisoned with NaF after a 4-week application of EGCG [92]. Numerous other studies available in the literature confirm the positive effects of green tea in cases of oxidative stress in the brains of laboratory animals poisoned with prooxidative substances ( Table 2).…”
Section: Phenolic Compoundsmentioning
confidence: 85%
“…Epigallocatechin gallate (EGCG) found in tea, particularly green tea, is a flavonoid characterized by very string antioxidative properties. A study revealed a very significant increase in the enzymatic and non-enzymatic antioxidative properties as well as a decrease of oxidative stress indicators in the brains of rats poisoned with NaF after a 4-week application of EGCG [92]. Numerous other studies available in the literature confirm the positive effects of green tea in cases of oxidative stress in the brains of laboratory animals poisoned with prooxidative substances ( Table 2).…”
Section: Phenolic Compoundsmentioning
confidence: 85%
“…Sodium fluoride-induced neurotoxicity in rats prevented by EGCG. Utilizing EGCG decreased ROS, TBARS, NO, and protein carbonylation levels, augmented GSH, TSH, and vitamin C activities, increased SOD, CAT, GPX, GST, GR, and G6PD activities, reduced TNF-α, NF-kB, and Fas mRNA expression, declined Bad and Bax, elevated Bcl-2 mRNA expression, attenuated caspase 3, caspase 8, and caspase 9 gene and protein expressions, protected DNA damage, and Nrf2/Keap might be involved (Shanmugam et al, 2018). 1-Methyl-4-phenyl-pyridinium induced neuronal damage in PC12 cells.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Consistent with this finding, several studies have observed that NO inhibits the molecular activity of renal NKA [232,313,316,317,318,319]. Several studies have also shown that F − induces NO synthesis in vivo [320,321,322,323,324,325,326]. Furthermore, experimental studies have shown that F − stimulates cGMP in the kidney and thyroid [327,328].…”
Section: Molecular Mechanisms By Which Fluoride Inhibits Na+ K+-amentioning
confidence: 69%